2020
DOI: 10.3389/fnsys.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Spinal Cord Stimulation After Chronic Complete Spinal Cord Injury Enables Volitional Movement in the Absence of Stimulation

Abstract: Restoration Spontaneous Movement After eSCS move without stimulation and those unable (p < 0.0005). The likelihood of recovery of spontaneous volitional control was correlated with spasticity scores prior to the start of eSCS therapy (p = 0.048). Volitional power progressively improved over time (p = 0.016). Additionally, cycling was possible without stimulation (p < 0.005). Conclusion: While some SVM after eSCS has been reported in the literature, this study demonstrates sustained restoration without active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 33 publications
(42 reference statements)
1
51
0
Order By: Relevance
“…Future work should also consider optimal rehabilitative interventions to combine with SCS. While there is ample pre-clinical evidence to suggest that SCS is more effective when combined with afferent feedback due to locomotor training [28][29][30], our study, and the recent clinical studies using epidural SCS [18,34], suggest that recovery of volitional motor control can occur when SCS is combined with simple exercises (incorporating descending volitional drive), which are cheaper and more accessible to the SCI population.…”
Section: Clinical Implications and Future Workmentioning
confidence: 67%
See 3 more Smart Citations
“…Future work should also consider optimal rehabilitative interventions to combine with SCS. While there is ample pre-clinical evidence to suggest that SCS is more effective when combined with afferent feedback due to locomotor training [28][29][30], our study, and the recent clinical studies using epidural SCS [18,34], suggest that recovery of volitional motor control can occur when SCS is combined with simple exercises (incorporating descending volitional drive), which are cheaper and more accessible to the SCI population.…”
Section: Clinical Implications and Future Workmentioning
confidence: 67%
“…No recovery (with tSCS off) was observed in P2, despite evidence of voluntary motor performance in the presence of tSCS during training sessions (see Video S1). Previous studies using epidural SCS in people with motor complete SCI have also reported considerable improvements in motor control (in the presence of SCS) in all participants (n = 12) [19,32,34], but recovery of volitional motor control with SCS off was only observed in a subset of these (5/12). Pre-clinical trials, using epidural SCS combined with step training, have also reported that animals with severe complete transections only show detectable improvements in stepping when stimulation is on, whereas animals with less severe injuries and greater lesion sparing were able to recover voluntary motor control when stimulation was absent [28][29][30]52].…”
Section: Recovery Of Volitional Motor Control (In the Absence Of Tscs)mentioning
confidence: 82%
See 2 more Smart Citations
“…Recovery relies on an intact central pattern generator (CPG) (106)(107)(108)(109)(110)(111) and often task-specific or locomotor training to engage the necessary proprioceptive and sensorimotor networks (112)(113)(114)(115)(116). Through EES and locomotor therapy in humans, many individuals have recovered some form of volitional sensorimotor control (10, 11, 27), although recent reports suggest that similar results can be achieved without the need for locomotor training (117,118).…”
Section: Ees To Restore Motor Function After Scimentioning
confidence: 99%